PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN BIPA DI ERA GLOBAL - Nadia Elfira Liyani; Nia Sri Wahyuni; Maulida Isefani; Sahrul Anwar; Lalu Tirta Bayu Tatthoa; Sakina Amelia; Baiq Rismarini Nursaly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has brought significant changes to the teaching of Indonesian for Foreign Speakers (BIPA), particularly in supporting a more flexible learning process that reaches learners in various countries. This article aims to describe the forms of digital media use in BIPA learning, analyze their benefits for language skills, and identify the challenges faced in their implementation. This study employs a descriptive qualitative method with a literature review approach, examining relevant books, journal articles, and proceedings. The findings show that digital media such as Zoom, Google Classroom, YouTube, Quizizz, Canva, and social media play a role in supporting listening, speaking, reading, and writing skills. The use of these media is able to increase learning motivation, expand access to learning resources, and facilitate more flexible interaction between teachers and learners. However, its implementation still faces obstacles such as limited internet access, digital literacy gaps, and minimal training for teachers. Therefore, the development of digital competence and the selection of appropriate media are needed so that BIPA learning becomes increasingly effective and adaptive to technological developments.